Chalcone derivatives as potential antiseptics and disinfectants - Krajišnik, Danina; Ivković, Branka; Božić, Dragana; Kotur-Stevuljević, Jelena; Vujić, Zorica (Archives of Pharmacy, 2022)
The global market for antiseptics and disinfectants is growing rapidly, fueled by a coronavirus pandemic and a possible outbreak of infectious diseases in the future. The antimicrobial, anti-inflammatory and redox activity of chalcone (1,3-diaryl-2-propen-1-one) is well documented in the literature. The aim of this study is screening of antimicrobial activity of chalcones and their saturated derivatives as active pharmaceutical ingredients, synthesized by Claisen-Schmidt condensation. The redox potential of the investigated compounds was tested in the biological environment using spectrophotometric methods to determine prooxidant/antioxidant parameters. Within preformulation studies solubility and compatibility with excipients commonly used in liquid pharmaceutical dosage forms was performed. All the tested chalcones and their saturated derivatives showed satisfactory antimicrobial activity, but two saturated chalcones showed the best MIC (0.156 - 1.25 mM) and were categorized as compounds with strong bacteriostatic activity. Solubility of the chalcons with moderate antimicrobial activity and redox potential was higher than its minimum bacteriostatic and bactericidal concentration in all the tested solvents (ethanol, isopropyl alcohol and propylene glycol). Based on the chemical structure and predicted logP values ​​for saturated chalcones that show stronger antimicrobial activity, better water solubility is expected. These data could be a starting point for formulations of antiseptics and disinfectants with lower concentrations of alcohol-based solvents, as the synergism between saturated chalcone and ethanol and isopropyl alcohol was previously shown. Considering the lighter color of the saturated chalcone, better aesthetic acceptability of the developed formulations is expected, since it will not stain the skin and objects during application.